Synergistic use of UAV surveys, satellite tracking data, and mark‐recapture to estimate abundance of elusive species - Stokes, Holly J.; Mortimer, Jeanne A.; Laloë, Jacques‐Olivier; Hays, Graeme C.; Esteban, Nicole (Ecosphere (Washington, D.C), 2023)
Estimating population abundance is central to many ecological studies and important in conservation planning. Yet the elusive nature of many species makes estimating their abundance challenging. Abundance estimates of sea turtles, marine birds, and seals are usually made when breeding adults are ashore, while life stages spent at sea, including as juveniles, are often poorly sampled. We used a combination of high‐resolution satellite tracking (Fastloc‐GPS), uncrewed aerial vehicle (UAV) surveys, and capture‐mark‐recapture approaches to assess the abundance of immature hawksbill (Eretmochelys imbricata) and green turtles (Chelonia mydas) in a tidal lagoon of the Chagos Archipelago (Indian Ocean). We captured, marked, and released 50 turtles (48 hawksbill and 2 green turtles) prior to UAV surveys and used satellite tracking data from 27 immature turtles (25 hawksbill and 2 green turtles) to refine the estimated numbers of marked turtles available for resighting and those likely to have emigrated from the study area. We estimated a total of 339 turtles in the lagoon with a density variation at different tidal heights between 265 turtles km−2 at high water and 499 turtles km−2 at low water. Of these, 91% were hawksbills and 9% were green turtles. These hawksbill densities are the highest reported among 17 foraging sites recorded around the world and likely reflect successful long‐term protection of turtles in the Chagos Archipelago.